Historical learning in History teaching: some considerations - Baumgarten, Lídia (Revista Crítica Histórica, 2022)
This article presents some reflections on the understanding of History teaching, its relation between the past and the present, a relation with daily life and the formation of a historical history of students from two classes of basic education in the municipality of Assis, state of São Paulo, in 2013. An activity with application of questionnaires, with open questions and some with alternative answers, being yes or no, and need to justify them. The selected classes were 7th Year of Elementary School, with a participation of 35 students and a 1st Year of High School, with eleven (11) participating students. It was used as a theoretical basis, such as Schmidt (2004), Cainelli (2006), Rüsen (1992), Guimarães (2003), Monteiro (2001) and Bittencourt (2005). As results, it is pointed out that the teaching of History develops as a central objective to instrument the student to produce his own knowledge. The social function of History must be to approximate its contents with the daily life of the student, thus providing a formation of Historical Critical-Genetic Consciousness (Rüsen, 1992).